Application of The Analysis System of the Effect of Cash Turnover, Receivables, and Inventory on Profitability in Cement Companies with the Rapid Application Development (RAD) Method - Rizaldy Khair; Khairunnisa Almadany (Sean Institute, 2022)
In general, every company has the goal of increasing the value of the company by maximizing profitability. Many factors can affect a company's profitability, namely per-round cash, receivables, and inventory. Therefore, it is necessary to build an application-based system that is able to analyze the effect of cash, receivables, and inventory turnover on profitability in the company automatically and in real time. In this study, it uses the DEA (Data Envelopment Analysis) method which can be viewed as an operator of multiple linear regression, in addition to the software system development method used, namely RAD (Rapid Application Development). This application system can determine the outcome of a negative or positive influence on profitability based on the variables between cash turnover, receivables, and inventory. This research was conducted on cement companies listed on the Indonesia Stock Exchange between 2018 and 2020. The data obtained from the measurement results can be used as an analysis of the next program situation by using test analysis using SPSS on the running system and turning it into an automation and realtime system. This Application System is built using the PHP programming language, and the CodeIgniter framework and uses a MySQL database server.